Methods of Training Teachers to use Electronic Information Education Resources and Their Flexibility - Zaripova Muslima Qurbonovna (Genius Publishing Group, 2022)
The article notes that it is convenient to use the hierarchical structure of information created, represented, visualized, processed, stored, transmitted and managed using information and telecommunication technologies.
Keywords: Digital textbook; interactive; science; concept